Sequential Copper‐Catalyzed Sonogashira Coupling, Hydroamination and Palladium‐Catalyzed Intramolecular Direct Arylation: Synthesis of Azepino‐Fused Isoindolinones. Issue 48 (29th December 2017) - Saini, Hitesh Kumar; Nandwana, Nitesh Kumar; Dhiman, Shiv; Rangan, Krishnan; Kumar, Anil
Abstract : A sequential copper‐catalyzed Sonogashira coupling followed by an intramolecular hydroamination and palladium‐catalyzed intramolecular direct arylation reaction was developed to provide a convenient and modular approach for the synthesis of useful azepino‐fused isoindolinones. Nineteen azepino‐fused isoindolinones were prepared in moderate to high (22–90 %) yields. The developed protocol tolerated various functional groups and involved the formation of one carbon–nitrogen and two carbon–carbon bonds in a one‐pot fashion. The palladium‐catalyzed intramolecular direct arylation step involved formation of an unusual eight‐membered palladacycle. Abstract : A modular synthesis of azepino‐fused isoindolinones has been developed in form of a sequential copper‐ and palladium‐catalyzed tandem reaction. The developed protocol involved the formation of one carbon–nitrogen and two carbon–carbon bonds in a one‐pot fashion. The palladium‐catalyzed intramolecular direct‐arylation step involves the formation of an unusual eight‐membered palladacycle.